Native plant composition and soil microfauna in limestone post-mining land as potential for development of ruminant forage - HARWANTO HARWANTO; PANCA DEWI MANU HARA KARTI; SUWARDI SUWARDI; LUKI ABDULLAH (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Harwanto, Karti PDMH, Suwardi, Abdullah L. 2023. Native plant composition and soil microfauna in limestone post-mining land as potential for development of ruminant forage. Biodiversitas 24: 6332-6342. Limestone post-mining land is a potential marginal land, through revegetation and integration, as a forage provider. Therefore, utilizing an exploratory systematic random sampling, this research explored the native botanical composition that had the potential for forage and soil microfauna associated with plants in the limestone post-mining land of PT Sinar Tambang Arthalestari, Banyumas, Central Java, Indonesia from June to September 2023. The results showed that the limestone post-mining soil had a slightly alkaline pH and low fertility. The botanical composition comprised 16 grasses, four legumes, and 21 forbs. Native plants that have the highest Importance Value Index (IVI) were grasses; Ischaemum rugosum, Imperata cylindrica, Paspalum scrobiculatum, and legumes; Mimosa pudica, Centrosema pubescens, and Calopogonium mucunoides. Grasses contained 8.35-12.61% Crude Protein (CP) and 42.50-50.78% Total Digestible Nutrient (TDN), while legumes contained 17.06-17.74% CP, 62.12-64.75% TDN. Mycorrhizal colonization and populations of Azotobacter, Azospirilum, and Rhizobium were associated with native plants in the rhizosphere. Conclusively, the grasses I. rugosum, I. cylindrica, P. scrobiculatum, and the legumes M. pudica, C. pubescens, and C. mucunoides have the potential to forage on limestone post-mining land and are associated with soil microfauna. However, soil fertility requires further improvement by applying organic matter, nitrogen, and phosphorus fertilizers.